Effect of Xiaoyao San on the brain-gut axis in rats after chronic immobilization stress - Liu, Qun; Ma, Qingyu; Liu, Yueyun; Li, Xiaojuan; Jiang, Youming; Yan, Zhiyi; Pan, Qiuxia; Li, Na; Bai, Xiaohui; Chen, Jiaxu (Journal of Traditional Chinese Medical Sciences, 2017)
To investigate the effect of Xiaoyao San on the brain-gut axis in rats exposed to chronic immobilization stress (CIS). Rats were divided into control, model, and treatment groups. The rats belonging to the model and treatment groups were subjected to CIS for 21 consecutive days, during which they were administered Xiaoyao San decoction [3.854 g/(kg·d)] or vehicle by gavage, and their body weight gain, food intake and water intake were monitored. The rats were subsequently subjected to the open field test (OFT) and d-xylose absorption test, and the expression levels of neuropeptides secreted by the hypothalamus and stomach were determined by enzyme-linked immunosorbent assay (ELISA), radioimmune analysis, or real-time fluorescence quantitative polymerase chain reaction. Gastric mucosal morphology was also assessed. The model rats exhibited complex brain-gut axis abnormalities following exposure to CIS, abnormalities signified by decreases in food intake, reductions in digestive absorption, decreases in body weight, decreases in the total distances traveled and increases in the time in the central zone during the OFT, gastric mucosal lesion development and decreases in gastrointestinal hormone secretion. These changes were reversed after treatment with Xiaoyao San, which also regulated the secretion of both peripheral (serum and stomach) and central (hypothalamus) brain-gut peptides. Specifically, the levels of neuropeptide Y (NPY) and neuropeptide Y receptor Y5, which are secreted by the hypothalamus and promote digestive function, were increased in the Xiaoyao San-treated group compared with the model group. Furthermore, the levels of pro-opiomelanocortin (POMC) and its receptor, melanocortin-4 receptor (MC4R), which are secreted by the hypothalamus and inhibit digestive function, were significantly decreased in the treatment group compared with the model group. However, the levels of ghrelin (GHRL), gastrin (GAS) and motilin (MTL), which are secreted by the stomach, were significantly increased in the serum and stomach of the treatment group compared with the serum and stomach of the model group following Xiaoyao San treatment (P < .05 vs. the model group). Xiaoyao San attenuates CIS-induced gastrointestinal dysregulation by regulating the peptides secreted by both the hypothalamus and the gastrointestinal tract (GIT), suggesting that its effects are associated with the brain-gut axis.